From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.